Granular encapsulation of light hydrophobic liquids (LHL) in LHL-salt water systems: Particle induced densification with quartz sand. (February 2016) - Boglaienko, Daria; Tansel, Berrin; Sukop, Michael C.
Abstract: Addition of granular materials to floating crude oil slicks can be effective in capturing and densifying the floating hydrophobic phase, which settles by gravity. Interaction of light hydrophobic liquids (LHL) with quartz sand was investigated in LHL-salt water systems. The LHLs studied were decane, tetradecane, hexadecane, benzene, toluene, ethylbenzene, m-xylene, and 2-cholorotoluene. Experiments were conducted with fine quartz sand (passing sieve No. 40 with openings 0.425 mm). Each LHL was dyed with few crystals of Sudan IV dye for ease of visual observation. A volume of 0.5 mL of each LHL was added to 100 mL salt water (34 g/L). Addition of one gram of quartz sand to the floating hydrophobic liquid layer resulted in formation of sand-encapsulated globules, which settled due to increased density. All LHLs (except for a few globules of decane) formed globules covered with fine sand particles that were heavy enough to settle by gravity. The encapsulated globules were stable and retained their shape upon settling. Polarity of hydrophobic liquids as the main factor of aggregation with minerals was found to be insufficient to explain LHL aggregation with sand. Contact angle measurements were made by submerging a large quartz crystal with the LHL drop on its surface into salt water. A positive correlation was observed between the wetting angle of LHL and the LHL volume captured ( r  = 0.75). The dependence of the globule density on globule radius was analyzed in relation to the coverage (%) of globule surface (LHL-salt water interface) by fine quartz particles. Graphical abstract: Highlights: Interaction of light hydrophobic liquids (LHL) with quartz sand was investigated. Formation of stable sand-encapsulated LHL globules in salt water was observed. Contact angles of 8 LHLs with quartz immersed in salt water were measured. A density-coverage model was produced for analysis of LHL densification by sand.